Documentários sobre as jornadas de junho de 2013: a polifonia dos protestos expressa em vídeo - Perrotti, Aline (2016)
This research analyses the discoursive interactions as well as the narrative paths of the Brazilian protests of June 2013 inside two documentaries. We start from the analysis of the constitutive elements in the expression plan, homologated in the contents plan, and investigates the construction of simulacrums of the mediatic addressers in the time of the protests. The corpus analyzed is composed of two movies, the first one being an independent production and the second one an institutional production: Com Vandalismo and Junho: o mês que abalou o Brasil. The enunciates contextualized sometimes on the streets sometimes by the narrators in debate, points out that the interrelations between the subjects Public Power, Society and Media, have built conflicting narrative programs. Similarly there is the presence of distinct objects of that value that, in most cases, as we see, did not have their possession achieved by the subjects protesters. Also from the figurativization we identify conflicts of interest between actors. We note that the construction of the actantial and thematic roles of social subjects of the protests operated by media addressers articulated changes in the discursive direction along the narrative path of the protests. In Com Vandalismo we have the subject (pacific-protester) and anti-subject (vandal-protester) competing for visibility on the streets, having been modalized by the breach of contract with the government and the provocative manipulation procedure of traditional media. These interactions lead us to believe that the relations between subjects in the protests present a population that lacks adequate political education to cope with their governments when they fail to comply with the democratic contract. In Junho: o mês que abalou o Brasil we have different strategies of manipulation that the traditional media had used during the period of the protests. The addresser Folha de S. Paulo uses the fiduciary already consolidated with their public to make-believe that all modalization performed by the mainstream media in the period converged with the "public opinion”. However, we observed that all modalizations performed by this addresser operated more in the order of veridiction about his own speech than in giving a political knowledge to the adressees; thus mobilizing many non-politicized subject to the protests, and generating dissemination of guidelines that resulted in transformations in the popular protests. We conducted this research in light of semiotics of Algirdas-Julien Greimas, sociossemiotics of Eric Landowski, in addition to studies of José Luiz Fiorin, Ana Claudia de Oliveira on significance and media interactions, and yet the film theorist Bill Nichols to treat the documentaries. The importance of this work rests on the fact that the journeys of June 2013 had been a landmark of political insurgencies in Brazil. We identify in the protests and discussions in the movies interactions that can base further research to understand other sociopolitical events that followed from that landmark, since it was found the great manipulative potential of the media, which makes people do things, even the not cognitively competencialized ones